Holistic housing concepts, design strategies and processes - Drexler, Hans (Hans Heinrich) 1972- (Edition detail, 2012)
Holistic Housing. Concepts, Design Strategies and Processes; is a fundamental reference work on housing construction. The book deals with the issue of sustainability in a planning context but also analyses a building?s usage and ageing over its ?life cycle?. A system of criteria specially developed in an accompanying research project can be used to compare and evaluate buildings. It can also be used as a tool for optimising the sustainability of buildings in development during the planning process. By contrast, most existing sustainability systems are conceived not as design and planning tools, but as instruments for evaluating finished buildings and completed planning. 15 practical examples explain the ways in which these criteria and other aspects of sustainable building can be implemented in sophisticated architecture and how these can then be experienced. A system developed from analysing the examples is used to classify and compare the buildings. The building?s significance as a lived environment is also not neglected here: sustainability develops in a dialogue between a building and its users, with an emphasis on residential usage.